PENERAPAN NILAI DEMOKRASI MELALUI PEMILIHAN KETUA OSIS DI SMP AGUS SALIM SEMARANG - Futura, Zakki; Supriyono, Supriyono; Suneki, Sri (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2026)
The purpose of this study is to examine how democratic values are applied in the election of the president of the student council at SMP Agus Salim Semarang and how this affects students' perceptions of democracy. Particularly in the contemporary day, when cultural identity is under threat, democracy teaching in schools is essential for forming students' moral fiber and political consciousness. The student council election is designed as a democratic mechanism encompassing various stages, such as socialization, candidate registration, campaigning, debates, voting, and inauguration, introducing democratic principles, including active participation, freedom of expression, transparency, and accountability. Using a qualitative approach, the findings show that this election not only selects a student leader but also serves as an effective medium for democracy education. Through this activity, students improve their political awareness, communication skills, tolerance, and critical thinking abilities. Therefore, the student council election at this school proves effective in helping shape students as citizens who value democratic principles and are prepared for active participation in community life.